Patellar Mobility in Elite Swimmers of Jorhat Swimming Society: A Cross-Sectional Study - N Victoria Chumthang; Ankur Jyoti Bora (International Journal of Orthopedic Nursing and Practices, 2025)
Background: Patellar mobility is vital for swimmers, affecting leg propulsion and injury risk. Understanding its role in swimming biomechanics enhances insights into knee stability and performance across different strokes. Aim: To assess patellar mobility in elite swimmers of Jorhat Swimming Society, Jorhat, Assam. Purpose: To explore the relationship between patellar mobility and swimming stroke styles, specifically focusing on knee biomechanics during the stroke. Methodology: A cross-sectional study involving 27 elite swimmers from Jorhat Swimming Society. Participants provided informed consent. The patella glide test was conducted to measure mobility, using a tape measure to record distances from the midpatella to the medial and lateral femoral epicondyles at 20° of knee flexion. Results: Analysis at a significance level of 0.05 revealed that the left patella had greater inferior mobility than the right (p=0.043). ANOVA showed significant differences in mobility across stroke styles, with hypomobility prevalent in superior and inferior directions (p=0.022). Backstroke and freestyle swimmers generally exhibited consistent patella mobility, ranging from 0.5 to 1.5 cm. Conclusion: This study shows variations in patellar mobility among elite swimmers, highlighting injury risks and the need for targeted interventions.
Keywords: Patellar mobility; breaststrokers; elite swimmers; knee flexion; knee pain